(untitled) (UMRAN - Journal of Islamic and Civilizational Studies, 2016)
Al-Ghazali (1055 till 1111) was a leading thinker who has made several idea related to finance, such as evolutionary theory of money, function of money, the prohibition of money hoarding, currency issues and the roles of government in a monetary system. Furthermore, the use of the currency at present often causes a variety of unhealthy economics situation. Thus, this study will describe the comparison between the roles of money in use today and the roles of money raised by al-Ghazali. Althought there was a fairly long period of time, the existence on the role of money is said to have continuity to the opinion of al-Ghazali. The study will analyze the extent to which the role of money raised by al-Ghazali can be applied to further improve the role of money in different economics system and how it is used to solve various economics problems that hit today.